Pola Pergerakan Monyet Ekor Panjang (macaca fascicularis) di Cagar Budaya Ciung Wanara - Srimulyaningsih, Reni; Suryadi, Lusi Desi Sriwulan (Fakultas Kehutanan Universitas Winaya Mukti, 2018)
Ciung Wanara Cultural Reserve (CWCR) is one of famous habitat of Long Tailed Monkeys (LTM). The existence of LTM is one of tourist attraction. But LTM in CWCR became depend on feed by tourists. This condition caused of pattern behaviour of LTM. The objective of this research is to know pattern behaviour of LTM in CWCR. The method of research is councentration count. The result of research is showing of LTM group. There are 4 groups of LTM in CWCR (Pangcalikan, Cikahuripan, Pamangkonan and Patimuan). The LTM pattern behaviour depends on alpha male of group. The pattern sleeping behaviour of LTM group is from the sleeping tree to returns to its sleeping tree. So, there is not overlap of each group, because source of feed, water and cover of LTM is sufficient. Keys words: Pattern behaviour, Long Tail Monkeys, Cultural Reserve